AN ECONOMIC ANALYSIS ON TRENDS AND GROWTH OF INDUSTRIAL SECTOR IN KARNATAKA - Chandrakala K S (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This article examines the growth and development trends in the industrial sector of Karnataka, a leading state in India in terms of industrial growth. The industrial sector plays a crucial role in the state’s economy and rural development, contributing significantly to employment generation, income improvement, GDP growth, and foreign exchange earnings. Karnataka is one of the fastest-growing states in India, with an industrial growth rate projected to be 4.8% in 2019-20, compared to a higher growth rate of 5.6% in 2018-19. The state’s industrial sector encompasses various industries, including mining and quarrying, manufacturing, construction, and electricity, gas, and water supply. The industrial structure of Karnataka is characterized by a mix of modern, high-tech, capital goods, and knowledge-intensive industries, alongside more traditional consumer goods industries. This blend highlights the state’s diverse industrial base, reflecting its overall economic progress. The study provides insights into the performance and growth trends of the industrial sector in Karnataka, analyzing the factors that have contributed to its development and the challenges that lie ahead in sustaining growth.